A new species of the genus Hippolyte (Decapoda: Caridea: Hippolytidae) from South China Sea and Singapore - Zhibin, Gan; Xinzheng, Li (Zootaxa, 2017)
A new species of hippolytid shrimp, Hippolyte ngi n. sp., is described and illustrated based on specimens collected from the Indo-West Pacific region. The new species clearly belongs to the ‘Hippolyte ventricosa H. Milne Edwards, 1837’ species complex, but is distinguished from its congeners by the dactylus of the last three pereiopods, the position of the hepatic spine, the proportions of the segments of the antennular peduncle, and other subtle but constant features.